Assessment of fatigue-related biochemical alterations in a rat swimming model under hypoxia - Shan, F.; Yang, T.; Li, J.; Huang, Q.-Y. (The Journal of Experimental Biology, 2019)
Hypoxia exposure alters the relative contribution of peripheral and central factors to exercise-induced fatigue, and central fatigue may play a predominant role in the decline in exercise performance under hypoxia.